Teenage, with child. - Ng, Jolin Zhuo Lin. (2010)
What do you do when you are teenage and pregnant? Teenage, with Child is an exploration of the phenomenon of teenage pregnancy, which has become increasingly problematic for society in recent years. What used to be the norm 30 or 40 years ago has become the exception in today’s context, particularly in Singapore where there is a growing trend of late marriages and delayed parenthood. The government calls for citizens to get married early and have more children—yet with an unplanned, teenage pregnancy, not only are these teens considered as too young to start families, that “order” is also reversed. The decision to be a mother weighs down heavily on a teen—she has to cope with added responsibilities of being a mum, a wife (if she marries), and keep on a brave face when others gossip and judge. By weaving in layers of personal stories, this feature attempts to understand the reasons aside from age and maturity that make teenage parenthood a concern for society. A second section is devoted to examining early marriages that stem from an unintended pregnancy. This feature also discusses the current efforts of welfare agencies that deal with teen pregnancy, as well as the existing sex education model.